An assessment of the health status by non-specific stress indicators in early farming populations from central and southern Africa - Dlamini, Nonhlanhla (Department of Human Biology, 2017)
The adoption of an agricultural lifestyle had profound implications for nutritional ecology, health and behaviour of human populations. The goal of this project was to generate information about the health status and disease patterns of early farming populations from central and southern Africa. Skeletal material was obtained from various 'Iron Age' sites in South Africa, Ingombe Ilede from Zambia, and Sanga and Katoto from the Democratic Republic of Congo. Palaeopathological analyses was done through the examination of non-specific stress indicators that included cribra orbitalia/porotic hyperostosis, Harris lines, linear enamel hypoplasias, subperiosteal bone lesions and dental diseases. The evidence from palaeopathology indicated that the environments played a major role in causing differences observed at micro-scale level. It is suggested that the health problems of these agricultural peoples are a result of their sedentary lifestyle and aggregation, which promoted maintenance and spread of infectious diseases; as well as high carbohydrate diets and dependence on a few main foodstuffs that affected their iron levels. The individuals from the forest region were less healthy than those in the dry or wet savanna zones. Also, the impact of the stress experienced by these societies was not sufficient to cause stunted growth and thus did not affect their terminal heights. The complex relationship between the environment, socio-cultural factors and biology has shown that subsistence economy only influences a fraction of human behaviour, health and well being. The results of this study argue that generalisations about prehistoric farming peoples cannot be made, until further research work is done.